2020
DOI: 10.1038/s41598-020-62885-0
|View full text |Cite
|
Sign up to set email alerts
|

Concepts of Double Hit and Triple Hit Disease in Multiple Myeloma, Entity and Prognostic Significance

Abstract: Risk assessment in newly diagnosed multiple myeloma patients (NDMM) is the first and the most crucial determinant of treatment. With the utilization of fiSH analysis as a part of routine practice, high riskMultiple Myeloma (MM) is defined as having at least one of the mutations related with poor prognosis including; t(4;14) t(14;16), t(14;20), del 17p, p53 mutation, gain 1q and del 1p. M-Smart MM risk stratification guideline by Mayo Clinic has proposed a concept similar to high grade lymphomas. Having two of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 19 publications
(18 reference statements)
2
33
0
1
Order By: Relevance
“…All the patients were followed up and the last follow-up time was April 30, 2020. To analyze the role of APBSCT as front-line therapy for myeloma with double-hit or triple-hit, we reviewed some published data [ 3 , 4 ] and compared our results with them. Statistical analysis was conducted using SPSS 22.0 software (SPSS, Chicago, IL).…”
mentioning
confidence: 99%
“…All the patients were followed up and the last follow-up time was April 30, 2020. To analyze the role of APBSCT as front-line therapy for myeloma with double-hit or triple-hit, we reviewed some published data [ 3 , 4 ] and compared our results with them. Statistical analysis was conducted using SPSS 22.0 software (SPSS, Chicago, IL).…”
mentioning
confidence: 99%
“…This eventually gives rise to highly aggressive subclones that expand to extramedullary sites and show high resistance to cytotoxic insults. For example, the presence of subclones harboring additional abnormality of chromosome 1q amplification and/or deletion of chromosome 17p is strongly associated with dismal outcomes [35,36,41,42]. Thus, in the absence of a universal molecular target in the background of high cytogenetic and molecular heterogeneity, clonal evolution is the critical biologic event to be prevented or overcome for improvement of therapeutic outcomes of patients with MM.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 62 Presence of more than one high-risk abnormality is seen in less than 5% of newly diagnosed MM including t(4;14), t(14;16), t(14;20), del(17p)/TP53 mutation, gain(1q), del(1p) and constitutes “double-hit” or “multi-hit“ myeloma, associated with significantly poorer prognosis. 91 , 92 Similarly, coexistence of del(6q) and del(1p32) with del(17p) significantly worsens the prognosis of patients. 60 …”
Section: Double Hit and Multiple Hit Myelomamentioning
confidence: 99%
“…17,62 Presence of more than one high-risk abnormality is seen in less than 5% of newly diagnosed MM including t(4;14), t(14;16), t (14;20), del(17p)/TP53 mutation, gain(1q), del(1p) and constitutes "double-hit" or "multi-hit" myeloma, associated with significantly poorer prognosis. 91,92 Similarly, coexistence of del(6q) and del (1p32) with del(17p) significantly worsens the prognosis of patients. 60 Conversely, using a genomic scar score (GSS), whole-genome sequencing studies have also identified a subgroup of MM patients characterized by low GSS (low mutational burden, specific mutation signatures pattern and fewer structural variants) and a very good overall survival.…”
Section: Double Hit and Multiple Hit Myelomamentioning
confidence: 99%